Dynamics of the Coreceptor-LCK Interactions during T Cell Development Shape the Self-Reactivity of Peripheral CD4 and CD8 T Cells - Horkova, Veronika; Drobek, Ales; Mueller, Daniel; Gubser, Celine; Niederlova, Veronika; Wyss, Lena; King, Carolyn G; Zehn, Dietmar; Stepanek, Ondrej (Cell reports, 2020)
Overtly self-reactive T cells are removed during thymic selection. However, it has been recently established that T cell self-reactivity promotes protective immune responses. Apparently, the level of self-reactivity of mature T cells must be tightly balanced. Our mathematical model and experimental data show that the dynamic regulation of CD4- and CD8-LCK coupling establish the self-reactivity of the peripheral T cell pool. The stoichiometry of the interaction between CD8 and LCK, but not between CD4 and LCK, substantially increases upon T cell maturation. As a result, peripheral CD8+ T cells are more self-reactive than CD4+ T cells. The different levels of self-reactivity of mature CD8+ and CD4+ T cells likely reflect the unique roles of these subsets in immunity. These results indicate that the evolutionary selection pressure tuned the CD4-LCK and CD8-LCK stoichiometries, as they represent the unique parts of the proximal T cell receptor (TCR) signaling pathway, which differ between CD4+ and CD8+ T cells.
Keywords: signální transdukce; Antigens; Cell Differentiation; tyrosinkinasa p56(lck), specifická pro lymfocyty; Protein Binding; TCR; antigeny; LCK; self-reactivity; myši inbrední C57BL; Signal Transduction; lymphocyte; signaling; T cell; CD4; Lymphocyte Specific Protein Tyrosine Kinase p56(lck); CD8; CD8-pozitivní T-lymfocyty; zvířata; homeostáza; evolution of the immune system; CD4-Positive T-Lymphocytes; vazba proteinů; buněčná diferenciace; CD4-pozitivní T-lymfocyty; CD8-Positive T-Lymphocytes; Homeostasis; thymus; Mice, Inbred C57BL; Animals